Cost-Utility Analyses of Cataract Surgery in Advanced Age-Related Macular Degeneration. Issue 2 (February 2016) - Ma, Yingyan; Huang, Jiannan; Zhu, Bijun; Sun, Qian; Miao, Yuyu; Zou, Haidong
ABSTRACT: Purpose: To explore the cost-utility of cataract surgery in patients with advanced age-related macular degeneration (AMD). Methods: Patients who were diagnosed as having and treated for age-related cataract and with a history of advanced AMD at the Department of Ophthalmology, Shanghai General Hospital, Shanghai Jiao Tong University, were included in the study. All of the participants underwent successful phacoemulsification with foldable posterior chamber intraocular lens implantation under retrobulbar anesthesia. Best-corrected visual acuity (BCVA) and utility value elicited by time trade-off method from patients at 3-month postoperative time were compared with those before surgery. Quality-adjusted life years (QALYs) gained in a lifetime were calculated at a 3% annual discounted rate. Costs per QALY gained were calculated using the bootstrap method, and probabilities of being cost-effective were presented using a cost-effectiveness acceptability curve. Sensitivity analyses were performed to test the robustness of the results. Results: Mean logarithm of the minimum angle of resolution BCVA in the operated eye increased from 1.37 ± 0.5 (Snellen, 20/469) to 0.98 ± 0.25 (Snellen, 20/191) (p < 0.001); BCVA in the weighted average from both eyes (=75% better eye + 25% worse eye) was changed from 1.13 ± 0.22 (Snellen, 20/270) to 0.96 ± 0.17 (Snellen, 20/182) (p < 0.001). Utility values from both patients and doctors increased significantly after surgery (p < 0.001 and p = 0.007). Patients gained 1.17 QALYs by cataract surgery in their lifetime. The cost per QALY was 8835 Chinese yuan (CNY) (1400 U.S. dollars [USD]). It is cost-effective at the threshold of 115, 062 CNY (18, 235 USD) per QALY in China recommended by the World Health Organization. The cost per QALY varied from 7045 CNY (1116 USD) to 94, 178 CNY (14, 925 USD) in sensitivity analyses. Conclusions: Visual acuity and quality of life assessed by utility value improved significantly after surgery. Cataract surgery was a cost-effective intervention for patients with coexistent AMD.